Uso de plasma rico em plaquetas em úlceras de córnea em cães - Merlini, N.B. [UNESP]; Fonzar, J.F. [UNESP]; Perches, C.S. [UNESP]; Sereno, M.G. [UNESP]; Souza, V.l. [UNESP]; Estanislau, C.A. [UNESP]; Rodas, N.r.; Ranzani [UNESP], J J.T. [UNESP]; Maia, L. [UNESP]; Padovani, C.R. [UNESP]; Brandão, C. V. S. [UNESP] (Universidade Federal de Minas Gerais, Escola de Veterinária, 2014)
This study aims to clinically and macroscopically evaluate the adjuvant therapy withplatelet-rich plasma in the form of eyedrops or clot, for corneal ulcers in dogtreated at the Veterinary Ophthalmology Service. We analyzed 20 eyes diagnosed withulcerative keratitis, divided into two experimental groups. The eyedrop group (GC)was composed of eyes treated topically with eyedrops of autologous platelet-richplasma (PRP), and the clot group (GT) was composed of eyes treated with aplatelet-rich clot and covered with a third eyelid for retention of the clot. Thegroups were evaluated by clinical and macroscopic analysis and by the analysis ofepithelial defect reduction, at different times, at three, five, ten, 15 and 30 days,except for the third day in GT. The coverage of the third eyelid was removed on thefifth day. In both groups the inflammation signs reduced, there was an improvement inocular sensibility and proper repair of epithelial defect. All GT eyes and 70% GCeyes showed complete healing on the fifth day, the remainder of GC completed healingon the tenth day. PRP in the form of eyedrops and clot is an excellent adjuvanttherapy to be instituted in the clinical treatment for corneal ulcer in dogs, becauseit decreases the inflammatory signs and the ocular pain and it potentially assists inhealing epithelial defects.

Este trabalho teve por objetivo avaliar, clínica e macroscopicamente, o tratamentoadjuvante com plasma rico em plaquetas na forma de colírio ou tampão, em úlceras decórnea de cães atendidos no Serviço de Oftalmologia Veterinária. Foram analisados 20olhos com diagnóstico de ceratite ulcerativa, distribuídos em dois grupoexperimentais. O grupo colírio (GC) foi constituído por olhos tratados topicamentecom colírio autólogo de plasma rico em plaquetas (PRP), e o grupo tampão (GT) porolhos submetidos ao tratamento à base de tampão sólido de PRP, associado aorecobrimento com terceira pálpebra para retenção deste. Os grupos foram avaliados,por meio de avaliação clínica, macroscópica e análise da redução do defeitoepitelial, em diferentes momentos, aos três, cinco, dez, 15 e 30 dias, com exceção doterceiro dia no GT. O recobrimento da terceira pálpebra foi removido no quinto dia noGT. Em ambos os grupos, houve redução dos sinais de inflamação, melhora nasensibilidade ocular e adequada reparação do defeito epitelial. Todos os olhos do GTapresentaram completa cicatrização no quinto dia e 70% no GC, atingindo a totalidadeno 10º dia. O PRP na forma de colírio ou tampão é uma excelente terapia adjuvante aser instituída no tratamento clínico da úlcera de córnea em cães, pois atua nadiminuição dos sinais inflamatórios, da dor ocular e auxilia potencialmente nacicatrização do defeito epitelial.
Use of platelet rich plasma on corneal ulcers in dogs
Keywords: Dogs; Epithelial defect; Growth factors; PRP; Cão; Defeito epitelial; Fatores de crescimento; PRP